Urea-based inhibitors of Trypanosoma brucei methionyl-tRNA synthetase: selectivity and in vivo characterization - Shibata, Sayaka (2012)
Urea-based methionyl-tRNA synthetase inhibitors were designed, synthesized and evaluated for their potential towards treating human African trypanosomiasis (HAT). With the aid of a homology model and a structure-activity-relationship approach, low nM inhibitors were discovered that show high selectivity towards the parasite enzyme over the closest human homolog. These compounds inhibit parasite growth with EC(50) values as low as 0.15 μM while having low toxicity to mammalian cells. Two compounds (2 and 26) showed excellent membrane permeation in the MDR1-MDCKII model, and encouraging oral pharmacokinetic properties in mice. Compound 2 was confirmed to enter the CNS in mice. Compound 26 had modest suppressive activity against T. brucei rhodesiense in the mouse model, suggesting that more potent analogs or compounds with higher exposures need to be developed. The urea-based inhibitors are thus a promising starting point for further optimization towards the discovery of orally available and CNS active drugs to treat HAT.